The effect of mechanical load cycling and polishing time on microleakage of class V glass-ionomer and composite restorations: A scanning electron microscopy evaluation - Mansoreh Mirzaie; Esmail Yasini; Hamid Kermanshah; Baharan Ranjbar Omidi (Wolters Kluwer Medknow Publications, 2014)
Background: Microleakage is one of the challenging concerns in direct filling restorations. Understanding of its related factors is important in clinical practice. The aim of this study was scanning electron microscopy (SEM) evaluation of marginal integrity in three types of tooth-colored restorative materials in class V cavity preparations and the effect of load cycling and polishing time on the microleakage. Materials and Methods: In this in vitro experimental study, class V cavity preparations were prepared on the buccal and lingual surfaces of 60 bovine incisors. The specimens were divided into three groups each containing 20 teeth: group 1: Filtek Z350, Group 2: Fuji IX/G Coat Plus, Group 3: Fuji II LC/GC varnish. In each group, 2 subgroups (n = 20) were established based on finishing time (immediate or delayed by 24 h). All specimens were thermocycled (×2,000, 5-50°C). In each sub groups, half of the teeth were load cycled. Epoxy resin replicas of 24 specimens were evaluated under field emission-SEM and interfacial gaps were measured. All teeth were then immersed in 0.5% basic fuchsin dye for 24 h, sectioned and observed under stereomicroscope. Data were analyzed with Kruskal-Wallis' test and Mann-Whitney U test and a comparison between incisal and cervical microleakage was made with Wilcoxon test. P < 0.05 was considered as significant. Results: Load cycling and filling material had a significant effect on microleakage, but polishing time did not. Cervical microleakage in Z350/load cycle/immediate polish and Fuji IX/load cycle/immediate or delayed polish and Fuji IX/no load cycle/immediate polish were significantly higher than incisal microleakage. Conclusion: It was concluded that the cervical sealing ability of Fuji IX under load cycling was better than Fuji II LC. Under load cycling and immediate polishing Z350 showed better marginal integrity than both Fuji II LC and Fuji IX. The immediate polishing didn't cause a statistically significant increase in microleakage of evaluated tooth-colored class V restorations.